Introduction to food - and airborne fungi (American Society for Microbiology Press, 2000)
The increasing interest among microbiologists in fungal contaminants of food and air has created the need to study these micro-organisms in more detail. Although fungi, producing toxins or which cause health hazards, are ubiquitous and belong to the common contamination flora, their recognition is hampered by incomplete and often confusing literature. This book, published by the Centraalbureau voor Schimmelcultures in the Netherlands and now available from ASM Press, serves as a guide to food- and airborne fungi and contains keys and morphological descriptions of the most common species.